FEATURES OF THE EFFECT OF TRIMETAZIDINE ON THE INDICATORS OF INFLAMMATION AND FIBROSIS IN PATIENTS WITH STABLE CORONARY ARTERY DISEASE WITH CONCOMITANT NON-ALCOHOLIC FATTY LIVER DISEASE - Fedorov, S.V.; Malinina, N.R.; Pozur, N.Z. (World of Medicine and Biology, 2025)
The issue of finding ways to optimize the treatment of patients with stable coronary artery disease in combination with non-alcoholic fatty liver disease is very relevant today. The aim of this study was to evaluate the effectiveness of drug therapy for coronary artery disease in combination with non-alcoholic fatty liver disease using trimetazidine, taking into account the effect on components of the low-intensity systemic inflammatory response, as well as the progression of fibrosis and steatosis. The study involved patients with combined pathology who, depending on the treatment they received, were divided into two groups. All patients underwent anamnestic, clinical, anthropometric, instrumental (abdominal ultrasound), and laboratory tests (complete blood count with leukocyte indices, determination of levels of high-sensitivity C-reactive protein, matrix metalloproteinase-6, galectin-3, and monocyte chemotactic protein-1). Patients in the second group received trimetazidine for one month. The use of trimetazidine improved exercise tolerance, slowed the progression of fibrosis and steatosis, reduced body mass index, and reduced the intensity of the systemic inflammatory response.
Keywords: stable coronary artery disease; non-alcoholic fatty liver disease; trimetazidine; inflammation; liver fibrosis